1980
DOI: 10.1083/jcb.85.3.682
|View full text |Cite
|
Sign up to set email alerts
|

Direct in vivo demonstration by radioautography of specific binding sites for calcitonin in skeletal and renal tissues of the rat.

Abstract: An in vivo binding assay using radioautography was employed to visualize calcitonin receptors in rat tissues . At 2 min after intravenous injection of biologically active '25 I-salmon calcitonin, free hormone was separated from bound hormone by intracardiac perfusion with lactated Ringer's followed by fixation with 2 .5% glutaraldehyde . Various tissues were removed and processed for light and electron microscope radioautography . These were compared to tissues removed from animals that received identical amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(83 citation statements)
references
References 18 publications
6
74
2
Order By: Relevance
“…Subsequent investigations have shown that the osteoclast [2][3][4][5] and renal tubular cells [6][7][8][9] are major target cells. Nevertheless, a number of other tissues possess CT receptors, including brain [10][11][12], lung [13], testes [14], and trout gill [15] as well as cell lines derived from a wide range of neoplasias including human breast [16], lung [17], and renal carcinoma [18], leukaemia [19,20], teratocarcinoma [21] and osteogenic sarcoma [22].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent investigations have shown that the osteoclast [2][3][4][5] and renal tubular cells [6][7][8][9] are major target cells. Nevertheless, a number of other tissues possess CT receptors, including brain [10][11][12], lung [13], testes [14], and trout gill [15] as well as cell lines derived from a wide range of neoplasias including human breast [16], lung [17], and renal carcinoma [18], leukaemia [19,20], teratocarcinoma [21] and osteogenic sarcoma [22].…”
Section: Introductionmentioning
confidence: 99%
“…Calcitonin is a peptide hormone produced by the thyroid parafollicular cells, commonly named 'C-cells,' that regulate calcium homeostasis (Warshawsky et al 1980). Increases in serum calcium activate the release of calcitonin from the C-cells, which consecutively inhibits bone resorption by the osteoclast and calcium absorption by the intestine.…”
Section: Calcitoninmentioning
confidence: 99%
“…The membranes were incubated with the reagent for 2 rnin on ice in a darkened room and then irradiated for 8 rnin with a Hanovia 140-W mercury arc lamp placed 15 cm from the membrane suspension. Tris/HCl (pH 7 h) ('hemic.ol method. Dissuccinimidyl suberate treatment was carried out using the method of Pilch and Czech [25].…”
Section: Membrane Solubilizationmentioning
confidence: 99%